G protein-coupled receptor signaling in VTA dopaminergic neurons bidirectionally regulates the acute locomotor response to amphetamine but does not affect behavioral sensitization. (15th December 2019) - Runegaard, Annika H.; Dencker, Ditte; Wörtwein, Gitta; Gether, Ulrik
Abstract: Amphetamine (AMPH) acts as a substrate of the dopamine transporter (DAT) and causes a dramatic increase in extracellular dopamine (DA). Upon entering DA neurons, AMPH promotes DA efflux via DAT through a mechanism implicating depletion of DA from vesicular stores, activation of kinase pathways and transporter phosphorylation. Despite the role of intracellular signaling for AMPH action, it remains elusive how the response to AMPH is affected in vivo by metabotropic regulation via G protein coupled receptor signaling pathways. Here, we show by employment of Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) that the acute hyperlocomotor response to AMPH is bidirectionally regulated by metabotropic input to VTA DA neurons with a markedly enhanced response upon activation of a Gs-coupled pathway and a markedly decreased locomotor response upon activation of a Gi-coupled pathway. The unique mechanism of action for AMPH was underlined by the absence of an effect of Gs activation on the locomotor response to the DAT inhibitor cocaine. Regardless of the profound effect on the acute AMPH response, repeated Gs activation or Gi activation did not affect development of AMPH sensitization. Furthermore, activation of a Gs-pathway or activation of a Gi-pathway in DA neurons did not have any effect on the AMPH-induced locomotor response in the AMPH sensitized mice. This suggests induction of alterations in DA neuronal functions that overrule the stimulatory or inhibitory effect of metabotropic input seen in drug-naïve mice. The data thereby underline the remarkable strength of maladaptive changes that occur upon intake of strong psychostimulants. This article is part of the issue entitled 'Special Issue on Neurotransmitter Transporters'. Highlights: Chemogenetic Gi-activation in dopamine neurons reduces AMPH-induced locomotion. Chemogenetic Gs-activation increases AMPH- but not cocaine-induced locomotion. Gs or Gi activation does not affect AMPH-induced behavioral sensitization. Gs or Gi activation does not affect AMPH-induced locomotion in sensitized mice. Sensitization causes cellular adaptions that surmount metabotropic regulation.